Information needed for optimal immunization related to medical advice: an observational prospective cohort study protocol (INFORMed) - Jennifer Wrenger; Bettina Berger; David D. Martin; David D. Martin; Ekkehart Jenetzky; Ekkehart Jenetzky (Frontiers Media S.A., 2024)
IntroductionToday, accessing information on health issues is easier than ever. However, the flood of information can make decision-making difficult. Information can influence the intention for an action, yet the action often remains unpredictable. It is unclear if there is a relationship between the intention behavior gap and the wish for medical advice in parents of newborns as they have to deal with a number of vaccinations more than any other group of people. According to survey data, vaccine-hesitant people have less interest in vaccine advice.Methods and designThis study aimed to validate and elaborate this finding in a specific population and in a prospective observational manner. This study protocol was registered: https://drks.de/search/en/trial/DRKS00030716, DRKS00030716. The specific objectives include a primary endpoint focused on the wish for advice among hesitant and non-hesitant parents. Secondary endpoints involve comparing parents in terms of their respective information needs, which will be assessed based on: (a) vaccination attitudes at 6 weeks, (b) actual action taken at 12 weeks, and (c) the consistency of their attitudes and decisions. Parents of infants up to 6-week-old will be recruited and asked before the first recommended vaccination period and thereafter when the infant is 12 weeks old. Participants will receive an online questionnaire focusing on the information and advice they would like to receive and have received. Vaccination attitudes will be assessed using the C7C questionnaire at 6 weeks and the actual action of taking the first vaccine at 12 weeks.DiscussionINFORMed will provide data on information needs and wishes of young parents depending on their attitude toward vaccination. Based on the results, health literacy in parents can be improved and information strategies can be adapted.